The international migration of health professionals - Michel Grignon; Yaw Owusu; Arthur Sweetman (Institute for the Study of Labor (IZA), 2012)
Health workforce shortages in developed countries are perceived to be central drivers of health professionals' international migration, one ramification being negative impacts on developing nations' healthcare delivery. After a descriptive international overview, selected economic issues are discussed for developed and developing countries. Health labour markets' unique characteristics imply great complexity in developed economies involving government intervention, licensure, regulation, and (quasi-)union activity. These features affect migrants' decisions, economic integration, and impacts on the receiving nations' health workforce and society. Developing countries sometimes educate citizens in expectation of emigration, while others pursue international treaties in attempts to manage migrant flows.
urn:nbn:de:101:1-201208096350
Keywords: J61; I15; I18; 330; migration; health professionals; international medical graduates; Gesundheitsberufe; Internationale Wanderung; Gesundheitsversorgung; Entwicklungsländer; Industriestaaten